Konstruksi Sosial Suami Istri tentang Tajdid Nikah - Wahyu Awaludin; Agus Purnomo; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2024)
This research aims to explore the dialectical process of couples who perform the practice of tajdid nikah in Cahya Makmur Village. This practice is typically motivated by reasons such as divorce, which encourages couples to reconcile; however, the findings of this study reveal that the motivations behind this practice are diverse, including concerns about divorce, efforts to maintain relationship harmony, economic difficulties, and family discord. Using a qualitative approach and field research methods, data were collected through interviews and documentation. The research findings indicate that the driving factors for tajdid nikah include a desire to improve economic conditions, caution in interpersonal relations, and the roles of P2UKD officials and the support of the village head in implementing this practice. Respondents believe that tajdid nikah serves as a solution to family problems, reporting increased peace of mind and improved economic conditions after performing tajdid nikah, with some even able to purchase private cars. This practice also positively impacts the mental health of respondents, creating a sense of peace and tranquility in their daily lives.